Instructional technology competencies as perceived by university lectures in Malaysia - Lam, Kim Wai; Hassan, Aminuddin; Sulaiman, Tajularipin; Kamarudin, Nurzatulshima (Human Resource Management Academic Research Society, 2018)
University lecturers’ perceptions of the importance and relevance of instructional technology competencies, as well as factors that contribute to instructional technology competencies required to enhance knowledge and delivery skills of university lecturers are examined in this study. A framework model is presented with the aim of revising and further developing curriculum competencies in tertiary education based on reviews on the philosophies and learning theories from past studies. In this regard, particular attention would be directed towards the Analysis, Design, Develop, Implement, Evaluate (ADDIE) instructional design model. It is proposed that by extending the ADDIE instructional design model to include three learning theories, namely the Behaviourist, Cognitive, and Constructivist theories, a suitable training programme for lecturers can be developed after taking into account their perceptions of instructional technology competencies. Students in institutions of higher learning would certainly benefit from lecturers who are able not only to design curriculums that are relevant to the demands of the marketplace, but, are also able to ensure that their delivery is effective and meets the needs of their students.